The effect of ecotype and planting location on properties and biofuels yield of big bluestem - Zhang, Ke (Kansas State University, 2014)
Renewable fuels derived from lignocellulosic biomass could reduce our dependence on fossil fuel resources and reduce greenhouse gas emissions. Big bluestem is an ecological-dominant warm-season (C4) perennial native grass that comprises as much as 80% of the plant biomass in prairies in the Midwestern grasslands of North America. Its high cellulosic content and low agricultural input recently have made big bluestem a promising feedstock for ethanol production. The overall goals of this study are to evaluate the potential of big bluestem in terms of ethanol production comparing with other native grasses by diluted sulfuric acid pretreatment and simultaneous sacchariﬁcation and fermentation and to understand the effects of ecotype and planting location on the chemical and elemental compositions and thermal properties as well as fermentable sugar yield of big bluestem along the Great Plains precipitation gradient. A total conversion efficiency of 79.2% and an ethanol concentration of 9.4 g/L were achieved after 72 h fermentation. About 0.262 kg (~0.332 Liters) ethanol could be produced from one kilogram dry mass of big bluestem under the present condition. Planting location had significant effects on chemical and elemental as well as specific heat, thermogravimetric parameters, high heating value and glucan mass yield. Ecotype had significant effects on glucan, xylan, lignin, and ash contents, and C, O, and H elemental fractions as well as specific heat, high heating value and glucan mass yield, whereas planting location significantly affected all measured variables. The ecotype-location interaction had significant effects on glucan, lignin, hydrogen contents and specific heat. Up to 97%, 88% and 80% of the variation in compositions can be explained by annual precipitation, growing degree days and potential evapotranspiration in 2010 respectively. Among all environmental factors, potential evapotranspiration had the most significant effect on thermal properties. Planting location had a stronger influence than ecotype and interaction between location and ecotype. Precipitation in 2010 possibly played a more significant role in divergence of glucan mass yield of the big bluestem.
Keywords: Big bluestem; Ecotype; Chemical composition; Elemental composition; Thermal properties; Ethanol; Biochemistry (0487)